PENGARUH MODIFIKASI PERMAINAN ENGKLEK TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK - Putra, Yustiar Rasyid Maulana; Supriatna, Eka; Gustian, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The athletic learning process especially the long jump squat styleÂ  in class XI based on observations made by the conditions experienced by students is mastery of basic technical skills that do not meet the minimum completeness criteria (KKM). The purpose of this study is to find out the effect of crank playing modification in squat style long jump learning. The research design used the experimental method of one-group desaign pretest-posttest design. The sampling technique in this study used purposive sampling technique, the number of participans was 32 students. Data collection techniques using test and measurements, the tool in the data collection is the squat-style long jump test with the grading-grading in the appendix. Data analysis using t-test analysis. Based on the results of data retrieval both the initial test or the final test of the study concluded : t-test analysis obtained the value of tiest 27,094 > accepted and Ho rejected means that there is an influence of learning crank playing on squat style long jumpa learning outcomes in students class XI significant. The percentage increase is as big as table 1,696, meaning that the hypothesis Ha is 40,62%.Â Keywords : Engklek Game, Long Jump Squat Style.